Determinants of Low Birth Weight Among Newborns at Debre Tabor Referral Hospital, Northwest Ethiopia: A Cross-Sectional Study - Mitiku Wale Muluneh MSc; Solomon Sisay Mulugeta MSc; Alebachew Taye Belay MSc; Yikeber Abebaw Moyehodie MSc (SAGE Publishing, 2023)
Introduction Low birth weight is one of the important predictors of perinatal survival, infant morbidity, and mortality, as well as the risk of developmental disabilities and diseases in the future. Objective(s) The study aimed to identify the associated factors of low birth weight among newborns at Debre Tabor referral hospital, Northwest Ethiopia. Methods A hospital-based cross-sectional study was conducted from January 1, 2021 to October 30, 2021 at Debre Tabor Referral Hospital. A total sample of 420 newborn birth records was considered. The binary logistic regression model was used to assess the associated factors of low birth weight. The results are presented as crude odds ratios and adjusted odds ratios (AOR) together with their corresponding 95% confidence intervals. Results In this study, 422 participants were included. Rural residence (AOR = 2.01; 95%CI 1.10-3.69), married marital status (AOR = 0.82; 95%CI 0.78-0.86), formal education (AOR = 0.79; 95%CI 0.67-0.92), smoking during pregnancy (AOR = 1.19; 95%CI 1.07-1.33), attended antenatal care (ANC) visits (AOR = 0.57; 95%CI 0.35-0.91), diabetes during pregnancy (AOR = 4.34; 95%CI 3.50-5.39), iron supplementation (AOR = 0.23; 95%CI 0.20-0.25), and maternal history of anemia (AOR = 5.87; 95%CI 2.67-12.89) were significantly associated with low birth weight of newborns. Conclusion This finding showed that residence, marital status, educational status, smoking during pregnancy, ANC visit, diabetes during pregnancy, iron supplementation, and mother's history of anemia were significantly associated with low birth weight. Therefore, policy makers and public health experts/practitioners should plan smoking preventive public health promotion campaigns. Furthermore, it is important that all health professionals properly manage the possible cause of LBW during pregnancy.